If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 2y = 4 Solving 10 + 2y = 4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 2y = 4 + -10 Combine like terms: 10 + -10 = 0 0 + 2y = 4 + -10 2y = 4 + -10 Combine like terms: 4 + -10 = -6 2y = -6 Divide each side by '2'. y = -3 Simplifying y = -3
| .75y-.66(0)=12 | | -2(3t-3)+3t=6t-5 | | 3+1.5(z+4)=3.5z-3 | | w-1.4=-6.3 | | 4a=3b-7 | | 5-3(x-3)=x+9 | | -2m+4=16+m | | 4x+y+x=180 | | 6(z+8)=5(z-2)+z | | 150=30-1p+9p | | 3=1.125X | | -16t^2+14t+270=0 | | -6x+7+7x=6+x+1 | | .75(0)-.66x=12 | | ae+n=p | | 0=2x^2+9x+4 | | 6k-(5+k)=-(3k+5) | | 3x^4-6x^3-2x^2=0 | | 2y^2-9y+8=0 | | 6n-22=-18+5n | | 12x+7=12x-5 | | x-.12x=503.23 | | 3t-17=-47+8t | | -3x-7y=14 | | 3(x-4)+4x-7=-3x+11 | | 2(10)-y=14 | | 5.5+2x=41.5 | | 19.9x+10=34+9.9x | | 3x^2+12=20x | | p=60-3q | | x=5-3y | | Y+(y+1)+(y+2)=45 |